Acute hemorrhagic edema of infancy: a worrisome presentation, but benign course - Alhammadi AH; Adel A; Hendaus MA (Dove Medical Press, 2013)
Ahmed H Alhammadi, Ashraf Adel, Mohamed A Hendaus Department of Pediatrics, Section of General Pediatrics, Hamad Medical Corporation, Doha, Qatar Abstract: Acute hemorrhagic edema of infancy (AHEI) is a benign type of leukocytoclastic vasculitis. It is a benign phenomenon although it manifests with fever, large palpable purpuric skin lesions, and edema. The presentation of AHEI can often resemble that of Henoch-Schönlein purpura. Since AHEI is a self-limited disease, conservative management is the most commonly followed approach. Our patient had complete resolution of AHIE without medical treatment. Keywords: infancy, hemorrhagic, edema